Avaliação do potencial de geração de biogás e de produção de energia a partir da remoção da carga orgânica de uma estação de tratamento de esgoto Estudo de caso - Faria, Rui Alexandre Pereira (2012)
The consequence of industrialization s growth and urbanization has resulted in effluents increased amount with high organic content, which are likely to cause serious negative environmental impacts and water bodies pollution. In doing so, promoting environmental sanitation, and still explore these wage treatment s energy potential, based on existing sanitation technology, maybe a viable alternative, the methane produced by organic matter s degradation could be piped and burned in engines generators, in order to minimize environmental impacts, enrich biogas as source of clean and renewable energy. In this case study, the analysis of the physical-chemical parameters served to verify the UASB s efficiency followed by two facultative ponds, estimate the biogas production and assess the potential for electric energy production in the years 2010and 2011. The system as a whole reached removal of organic load s rates around 82% of COD, BOD and 81% in 2010and 83% and 87% of COD and BOD, respectively, in 2011, with estimated average production biogas of 513and 702m3 biogas/day in the years 2010 and 2011, respectively. The results indicated a significant potential for biogas production from the organic load s removal, with the possibility of harnessing energy from a renewable source.